Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Inkuiri Terbimbing Pada Materi Momentum, Impuls Dan Tumbukan Kelas X Madrasah Aliyah - Roza, Media (Universitas Islam Negeri Imam Bonjol Padang, 2017)
Student worksheets (SWS) is one of the teaching materials that can activate learners, help find the concept and make it easier to understand the subject matter. Based on the results of observation obtained information that the teacher used the teaching materials of printed books and gita but not yet the availability of teaching materials that already contain learning steps in accordance with K-13. In response to these conditions developed teaching materials in the form of SWS Based Guided Inquiry. The purpose of this study is the production of teaching materials in the form of SWS Based Guided Inquiry on Momentum, Impulse and Collision materials valid, practical, and effective. This study was conducted 4-D model, define, design, develop, and disseminate. SWS Validity Test obtained value 90 % with very valid category. Practicality by 6 learner was obtained by value 89.02% with very practical category, practice by 20 learner was obtained by value 86.02% with very practical category and by teacher obtained result 89.16 % with very practical category. The effectiveness obtained result with value 92.22% with very effective category. Based on research obtained conclusion of SWS based guided inquiry on the material of mementum, impulse and collision valid, practical and effective.